Donald Trump’s and Hillary Clinton’s Interruptions In Presidential Debates - Zuliati Rohmah; Alda Fitriani Suwandi (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2021)
The present research aims to investigate the types and functions of interruptions of Donald Trump and Hillary Clinton during the US presidential debates in 2016. Data collected from Donald Trump's and Hillary Clinton's speech in the debates were transcribed and analyzed to find types and functions of interruptions by both of the candidates. The results of the Conversational Analysis display that Donald Trump dominates the interruptions by applying a substantially greater number of interruptions consisting three different types of interruptions. Butting-in Interruptions were applied by both as the biggest number of interruptions. Data analysis also demonstrates that intrusive functions appear much more frequently compared to the collaborative functions of interruptions applied by the male and female presidential candidates. Discussion as to why such phenomena are noticeable in the data concludes the paper.